Rise of the rocket girls [book club bag] : the women who propelled us, from missiles to the moon to Mars - Holt, Nathalia, 1980- (Little, Brown and Company, 2016)
During World War Il, when the brand-new minted Jet Propulsion Laboratory needed quick-thinking mathematicians to calculate jet velocities and plot missile trajectories, they recruited an elite group of young women--known as "computers"--who, with only pencil, paper, and mathematical prowess, transformed rocket design and helped bring about America's first ballistic missiles. But they were never interested in developing weapons--their hearts lay in the dream of space exploration. So when JPL became part of a new agency called NASA, the computers worked on the first probes to the moon, Venus, Mars, and beyond. Later, as digital computers largely replaced human ones, JPL was unique in training and retaining its brilliant pool of women. They became the first computer programmers and engineers, and through their efforts, we launched the ships that showed us the contours of our solar system. For the first time, this book tells the stories of these women who charted a course not only for the future of space exploration but also for the prospects of female scientists. Based on extensive research and interviews with the living members of the team, Rise of the Rocket Girls offers a unique perspective on the role of women in science, illuminating both where we've been and the far reaches of where we're heading.--Adapted from dust jacket.